Features of the Clinical Presentation of Epileptic Seizures and Neurological Syndromes of the Consequences of Brain Injury Depending on the Severity of Post-Traumatic Epilepsy (Eurasian Medical Research Periodical, 2022)
The problem of diagnosis and drug treatment of post-traumatic epilepsy remains one of the most challenging tasks in clinical neurology. Despite the progress made, many aspects of modern diagnosis and adequate treatment of the disease remain unresolved. The clinic of post-traumatic epilepsy requires further study. The etiological role of mild traumatic brain injury in the genesis of this condition has not been definitively established. The prognosis of posttraumatic epilepsy after traumatic brain injury and the advisability of preventive therapy with anti-epileptic drugs (AEDs) in these patients to reduce the risk of the disease remain unresolved. The informative value of new highly sensitive electrophysiological (video-eEG monitoring) and neuroimaging (magnetic resonance spectroscopy and positron emission tomography) instrumental studies in diagnosing the disease and indications for their use have not been established. The efficacy of combination therapy with antiepileptic and neuroprotective drugs has not been studied. This is the cause of late diagnosis and untimely treatment in patients with post-traumatic epilepsy. As a result, the number of patients with a pharmacoresistant course of the disease, personality changes, intellectual and mental disorders, social disadaptation, a sharp deterioration in the quality of life significantly increases